The main life stressors of secondary school students during Movement Control Order (MCO) in Sabah, Malaysia - Walton Wider; Bee Seok Chua; Jasmine Adela Mutang; Janeta Anthony; Chit Thet Lal Oo; Cho Chiew Tan; Rosnah Ismail; Lester Naces Udang (EnPress Publisher, LLC, 2024)
The COVID-19 pandemic prompted global crises and enforced strict measures like the Movement Control Order (MCO) in Malaysia, significantly impacting societal norms, particularly affecting secondary school students. The current study employs a qualitative methodology to determine how COVID-19 affects the life stress experienced by secondary school students. Secondary school students were recruited in Sabah, Malaysia, from April to August 2022, after Malaysia entered the endemic phase on 1 April 2022. As part of a larger survey, students were asked to respond to an open-ended question about life stressors they face as a result of the pandemic COVID-19 or during home-based teaching and learning (PdPR). A total of 1069 secondary school students from various backgrounds were included in the study. However, only 714 students responded to the open-ended question. The pattern of meaning across the texts was determined using Birks and Mills’s method of multilevel coding. The students’ perspectives on life stressors were classified into five broad categories: restriction stress, emotional stress, online study stress, family-related stress, and others-related stress. Restriction stress, which refers to being confined at home, restricted movement, hampered family, friendship, and outdoor activities, and no freedom were rated as the most significant life stressors associated with the COVID-19 pandemic by students. This research provides valuable insights for policymakers, educators, and parents, emphasizing the profound effect of pandemic-induced restrictions on student life and the essential role of targeted interventions in fostering resilience among students.